Environment and livelihoods in tropical coastal zones [ managing agriculture-fishery-aquaculture conflicts - Chu, Thai Hoanh , 1949- (Comprehensive assessment of water management in agriculture series, 2006)
This book focuses on the challenges people face in managing agricultural crops, aquaculture, fisheries and related ecosystems in inland areas of coastal zones in the tropics of Asia, Africa, Australia and South America. These challenges can create conflcts in the use of natural resources between different stakeholders.